About Death: Matter, Image and Logos within the Limits of Representation - Takkal Fernández, Aixa; Rubio Garrido, Alberto (Eikón / Imago, 2021)
This reflection addresses the phenomenon of death and the problematics related to its representation; both in visual language, as from a theoretical- conceptual approach. With the aim of thinking from the concrete, a hermeneutical approach is ventured to the last graphic work of the outsider painter Martín Ramírez. In the field of theory, some concepts presented in Martin Heidegger's philosophy, such as finitude, death, anguish and nothingness will be expounded. The methodological strategy involves establishing an interdisciplinary discourse, in a close critical dialogue with the rationalist tradition and the metaphysics of Modernity but maintaining the precaution of not reducing or subordinating the analysis of the visual work to the theoretical frame. The approach, transversal to the entire article, starts from the hypothesis that certain reluctant condition to being representated is intrinsic to the phenomenon of death.